The Restoration of Altars in the 1630s - Fincham, Kenneth ca. 20./21. Jh. (The historical journal, 2001)
The nationwide campaign to erect railed altars in the 1630s has always been seen as a central feature of the Laudian reformation of the Church. Recently some scholars have denied its close association with Laud and Arminian sacramentalism, and have proposed that the policy originated with Charles I, to be reluctantly endorsed by his archbishop. As for its enforcement, Julian Davies has identified at least five variants which were implemented in the dioceses. This article argues instead that Archbishops Neile and Laud were centrally involved in the introduction of the railed altar, and that they oversaw the imposition of a single altar policy, with only Williams of Lincoln briefly championing a variation on it. Differences did emerge, however, over where communicants should receive, since this had not been prescribed by authority. Charles I, on this reading, was not the driving force for change, although he clearly came to support it.